Sadness, Depression, and the Dark Night of the Soul : Transcending the Medicalisation of Sadness. - Durà-Vilà, Glòria (Jessica Kingsley Publishers, 2017)
This ground-breaking book contemplates how some religious individuals and communities conceptualise severe sadness and emotional distress, which might otherwise be described as pathological, as an essential ingredient for spiritual development. It explores the implications this may have for clergy and psychiatrists seeking to understand sadness.